Intron definition and a branch site adenosine at nt 385 control RNA splicing of HPV16 E6*I and E7 expression. - Masahiko Ajiro; Rong Jia; Lifang Zhang; Xuefeng Liu; Zhi-Ming Zheng (PLoS ONE, 2012)
HPV16 E6 and E7, two viral oncogenes, are expressed from a single bicistronic pre-mRNA. In this report, we provide the evidence that the bicistronic pre-mRNA intron 1 contains three 5' splice sites (5' ss) and three 3' splice sites (3' ss) normally used in HPV16(+) cervical cancer and its derived cell lines. The choice of two novel alternative 5' ss (nt 221 5' ss and nt 191 5' ss) produces two novel isoforms of E6E7 mRNAs (E6*V and E6*VI). The nt 226 5' ss and nt 409 3' ss is preferentially selected over the other splice sites crossing over the intron to excise a minimal length of the intron in RNA splicing. We identified AACAAAC as the preferred branch point sequence (BPS) and an adenosine at nt 385 (underlined) in the BPS as a branch site to dictate the selection of the nt 409 3' ss for E6*I splicing and E7 expression. Introduction of point mutations into the mapped BPS led to reduced U2 binding to the BPS and thereby inhibition of the second step of E6E7 splicing at the nt 409 3' ss. Importantly, the E6E7 bicistronic RNA with a mutant BPS and inefficient splicing makes little or no E7 and the resulted E6 with mutations of (91)QYNK(94) to (91)PSFW(94) displays attenuate activity on p53 degradation. Together, our data provide structural basis of the E6E7 intron 1 for better understanding of how viral E6 and E7 expression is regulated by alternative RNA splicing. This study elucidates for the first time a mapped branch point in HPV16 genome involved in viral oncogene expression.